Docking control on both stationary and moving stations based on docking formation. Issue 6 (1st March 2014) - Kwon, Ji‐Wook; Seo, Jiwon
Abstract : A docking control algorithm of a non‐holonomic mobile agent is proposed, which can be employed in both the stationary and the underway docking stations. To this end, a leader–follower docking formation is proposed, where the size of the formation is reduced until docking surfaces of the agent and the docking stations contact each other. Also, a feedback linearisation control law that can compensate for the input constraint is implemented to maintain the docking formation. Numerical simulations are included to show the performance of the proposed docking control algorithm.